Raising the Young Athlete: Training and Injury Prevention Strategies: Current Concept Review - Bank, Nicholas; Hecht, Christian; Karimi, Amir; El-Abtah, Mohamed; Huang, Lauren; Mistovich, R. Justin (Journal of the Pediatric Orthopaedic Society of North America, 2022)
Participation in youth sports is at an all-time high, surpassing pre-pandemic levels. While this represents a growing opportunity for increased activity, socialization, and skill development in America’s young athletes, we must remain cognizant of the associated risks that threaten their long-term physical and psychological well-being. To optimize the risk-benefit ratio of the increasing involvement in organized sports, current sporting safety recommendations are needed. We sought to provide current concepts on optimal training methods, injury prevention strategies, and stakeholder education programs.